REAKSI PASAR TERHADAP MALE-TO-FEMALE CHIEF EXECUTIVE OFFICER TURNOVER - Primasari, A. A. Paramita; Sukartha, I Made (E-Jurnal Akuntansi; Vol 16 No 2 (2016), 2016)
This study aimed to determine market reaction after male-to-female (MTF) CEO turnover announcement and compared it with market reaction after male-to-male (MTM) CEO turnover announcement. This research was conducted on companies on Indonesian Stock Exchange which did MTF and MTM CEO turnover during 2004 – 2014. The total sample is 35 companies with respectively 18 MTF and MTM CEO turnover announcements. The sampling method used was purposive sampling. The test result showed that there was no negative abnormal return on shares in companies that announced MTF CEO turnover which means the market did not react negatively to the presence of female CEOs. There was also no difference in abnormal return between the shares of firms that did MTF and MTM CEO turnover which means investors did not distinguish their investment decisions based solely on gender of CEOs.
Keywords: Market Reaction; Gender; Discrimination; Male-To-Female CEO Turnover; Male-To-Male CEO Turnover